Le conseil psychologique et d'orientation: jalons pour un modèle psychosocial intégre - Fahmy, Pauline (Canadian Journal of Counselling and Psychotherapy, 2012)
Guidance counselling was meant at its beginnings, as an aid for social in of people through their choice and practice of an occupation which could guarantee their own development and the development of their society. The theoretical foun- dations of counselling have been drawn essentially from the mental hygiene movement and psychotherapy, and the practice has evolved from functional humanism to individualistic humanism. We advocate the use of sociological information and social psychology concepts in order to broaden the scope of counselling. This broadening means that: 1) counselling is considered relevant for all the life situations with some potential developmental risks 2) the means and goals of counselling are reorganized in order to include the concept of "political maturity" without which there is no "psychological maturity".